Patient Experience of Wearing Compression Garments Post Burn Injury: A Review of the Literature. Issue 4 (July 2017) - Coghlan, Nicole; Copley, Jodie; Aplin, Tammy; Strong, Jenny
Abstract : This review was conducted to critically appraise the literature regarding the patient's lived experience of, and adherence to, wearing compression garments post burn injury. Scholarly articles were identified from searches of the following databases: Pubmed, Cochrane Central, CINAHL, PsycINFO, and OT Seeker. Combinations of key words including compression therapy/garment, pressure therapy/garment, burn(s), adherence, and patient experience were utilized. Retrieved studies were included in the review if they were written in English, reported on adult burn populations, and the patient's lived experience of wearing compression garments. Included studies were critically appraised and content analysis was completed on the results sections of the two qualitative studies. Nine studies investigating patient's lived experiences were retained: one systematic review, one randomized controlled trial, five cross-sectional surveys, and two qualitative studies. An adherence framework provided a conceptual basis to categorize reported patient's lived experiences. Results identified a strong focus on patient and treatment-related experiences with limited investigation of condition, patient-provider and health care system experiences. Minimal investigation has been completed regarding the impact of these patient's lived experiences on the adherence to wearing compression garments. Additional research using qualitative methods is required to gain a deep understanding of patient's experiences and perspectives of wearing compression garments and how these experiences influence on their adherence to wearing them. Identification of key experiences that lead to patients removing their compression garments may lead to modification of treatment and system approaches to better align with patients' needs and development of potential interventions that promote adherence.